CEO's education and investment–cash flow sensitivity: an empirical investigation. Issue 4 (23rd December 2020) - Gupta, Gaurav; Mahakud, Jitendra; Verma, Vivek
Abstract : Purpose: The purpose of this study is to examine the impact of financial and technical education of chief executive officer (CEO) on investment–cash flow sensitivity (ICFS) of Indian manufacturing firms. Design/methodology/approach: The study uses the dynamic panel data model and more specifically, the system-generalized method of moments (GMM) technique to investigate the effect of CEOs' education on ICFS of Indian manufacturing firms during the period 1998–1999 to 2016–2017. Findings: The study shows that financial (technical) education of CEOs does (not) affect ICFS. The results explain that the role of the CEO's education in ICFS is highly significant during the crisis period. The robustness test depicts that the influence of financial education on ICFS is less (more) for group-affiliated and large-sized firms (stand-alone and small-sized firms). Further, the CEO's education is significantly associated with corporate investment decisions. Research limitations/implications: Due to the unavailability of the CEO's compensation data for the selected sample, future research could explore the impact of CEO's education with respect to CEO's compensation on ICFS. Practical implications: First, the authors find that financially educated CEOs affect ICFS; therefore, firms should take care of CEO's education during recruitment of CEOs. Second, lending agencies should also consider the educational background of the CEO before approval of funding to make it safe. Third, investors should keep in mind the educational background of the CEO for the growth of their investment as it may be easier for financially educated CEOs to borrow from the market at the time of requirement. Originality/value: This study contributes to the existing literature by providing empirical evidence through analyzing the impact of a CEO's education on ICFS in the context of India. This study is very unique in itself as it uses the sample of manufacturing sectors of India, which are growing very fast and attracting global investors to create a global hub of manufacturing in India. This study also considers different types of education such as financial and technical education of CEOs in the context of a developing economy like India. This study made its findings robust across company characteristics and periods based on the financial crisis.